Corticobasal Degeneration: A case report - Gómez P., Juan Pablo (Revista Chilena de Fonoaudiología, 2015)
A case study of corticobasal degeneration in a Chilean 48MyearMold female patient is reported. The clinical course was progressive and included Parkinsonism (rigidity, akinesia, postural abnormalities, dysarthria), cognitive impairment, dressing apraxia, constructive apraxia and hypomimia. In addition, the patient had nonMfluent aphasia. Also, the patient was diagnosed with Chronic Depressive Syndrome and Deep Venous Thrombosis (DVT) of the left lower extremity. In recent decades, several types of neurodegenerative diseases have been described. These diseases have different clinical and pathologic features. However, in practice, it is difficult to differentiate them from one another and, to reach an accurate diagnosis, advanced medical skills, detailed clinical evaluations of neuroimaging and laboratory studies are needed. “Tauopathies”, which are Corticobasal Degeneration (CBD) and Progressive Supranuclear Palsy (PSP) are among the major neurodegenerative diseases occurring with Parkinsonism.